An anti-crystallization design of selective catalytic reduction nozzle holder. (May 2021) - Liu, Dewen; Lu, Kai; Liu, Shusen; Wu, Yan; Bai, Shuzhan
From the aspect of reducing the risk of crystallization on nozzle surface, a new design of nozzle protective cover was to solve the problem in selective catalytic reduction (SCR) urea injection system. The simulation calculation and experimental verification methods were used to compare different schemes. The results show that reducing the height of nozzle holder can reduce the vortex currents near nozzle surface and effectively reduce the risk of crystallization on the nozzle surface. It is proposed to install a protective cover in the nozzle holder under the scheme of reducing the height of nozzle holder, which can further eliminate the vortex. Simulation and test results demonstrate good agreement under the rated running condition. The scheme of adding a protective cover in the nozzle holder shows the least crystallization risk by computational fluid dynamics (CFD) method. The crystallization cycle test shows that, after the height of nozzle holder is reduced, the risk of crystallization on the nozzle surface is reduced correspondingly. The addition of a protective cover in the nozzle holder solves the problem of crystallization on the nozzle surface, which provides a new method for anti-crystallization design.